Cu nanowires modified with carbon-rich conjugated framework PTEB for stabilizing lithium metal anodes. Issue 99 (1st December 2021) - Yang, Shan; Xiao, Ru; Zhang, Tongwei; Li, Yuan; Zhong, Benhe; Wu, Zhenguo; Guo, Xiaodong
Abstract : The carbon-rich conjugated framework PTEB is employed to modify Cu nanowire arrays for stabilizing Li anodes. A high CE (over 99%) and long lifespan (over 800 h) are achieved. The rich acetylene bonds serve as lithiophilic sites and 3D nanowire array structure promotes uniform Li + flux. Abstract : Lithium metal anodes provide a direction for the development of high-energy-density lithium-ion batteries. To overcome lithium dendritic growth and low Coulombic efficiency in lithium plating/stripping processes, the design of a three-dimensional (3D) host structure is a feasible solution. Herein, copper nanowires in situ -coated with a carbon-rich conjugated framework, poly(1, 3, 5-triethynylbenzene), and grown on copper foam were constructed as a 3D lithium host, and shown to effectively yield a low nucleation overpotential, smooth lithium deposition, and improved cycling stability. This well-designed 3D host structure achieved a high Coulombic efficiency of over 99% for 150 cycles and showed reversible lithium plating/stripping stability for over 800 h at 2 mA cm −2 . This work has highlighted the benefits of using an interface modification strategy, and provided a feasible route for 3D host structure design in the development of lithium metal anodes.